Tantangan Dalam Menegakkan Hukum Pada Kasus Kekerasan Seksual: Studi Tentang Victim-Blaming pada Polisi - Vita Valia; Fathul Lubabin Nuqul (Journal Psikologi Forensik Indonesia, 2024)
This study investigates the challenges of enforcing laws related to sexual violence in Indonesia, with a focus on victim-blaming practices within law enforcement. Despite the critical role of police in ensuring justice for victims of sexual violence, cultural and institutional biases often undermine legal processes. Drawing on qualitative phenomenological methods, the research involved semi-structured interviews and observations with four police officers (one male, three female) to explore their perceptions, attitudes, and practices in handling sexual harassment cases. Findings reveal a dissonance between the informants’ theoretical recognition of structural factors (e.g., broken homes, low education, and socioeconomic vulnerabilities) and their victim-blaming behaviors during investigations. These behaviors, rooted in patriarchal norms and gender stereotypes, manifest in skepticism toward victims’ credibility, attribution of blame based on attire, behavior, or consensual relationships, and inadequate investigative rigor. Such practices perpetuate secondary victimization, deter reporting, and compromise the fairness of legal outcomes. The study underscores the urgent need for systemic reforms, including gender-sensitive training for law enforcement, stricter accountability mechanisms to address biased practices, and enhanced victim-centered support systems. By addressing these challenges, institutions can foster equitable justice delivery and mitigate the retraumatization of survivors.